Free water elimination improves test–retest reproducibility of diffusion tensor imaging indices in the brain: A longitudinal multisite study of healthy elderly subjects. Issue 1 (13th August 2016) - Albi, Angela; Pasternak, Ofer; Minati, Ludovico; Marizzoni, Moira; Bartrés‐Faz, David; Bargalló, Núria; Bosch, Beatriz; Rossini, Paolo Maria; Marra, Camillo; Müller, Bernhard; Fiedler, Ute; Wiltfang, Jens; et al.
Abstract: Free water elimination (FWE) in brain diffusion MRI has been shown to improve tissue specificity in human white matter characterization both in health and in disease. Relative to the classical diffusion tensor imaging (DTI) model, FWE is also expected to increase sensitivity to microstructural changes in longitudinal studies. However, it is not clear if these two models differ in their test–retest reproducibility. This study compares a bi‐tensor model for FWE with DTI by extending a previous longitudinal‐reproducibility 3T multisite study (10 sites, 7 different scanner models) of 50 healthy elderly participants (55–80 years old) scanned in two sessions at least 1 week apart. We computed the reproducibility of commonly used DTI metrics (FA: fractional anisotropy, MD: mean diffusivity, RD: radial diffusivity, and AXD: axial diffusivity), derived either using a DTI model or a FWE model. The DTI metrics were evaluated over 48 white‐matter regions of the JHU‐ICBM‐DTI‐81 white‐matter labels atlas, and reproducibility errors were assessed. We found that relative to the DTI model, FWE significantly reduced reproducibility errors in most areas tested. In particular, for the FA and MD metrics, there was an average reduction of approximately 1% in the reproducibility error. The reproducibility scores did not significantly differ across sites. This study shows that FWE improves sensitivity and is thus promising for clinical applications, with the potential to identify more subtle changes. The increased reproducibility allows for smaller sample size or shorter trials in studies evaluating biomarkers of disease progression or treatment effects. Hum Brain Mapp 38:12–26, 2017 . © 2016 Wiley Periodicals, Inc.